Cosmic-generative architecture PhilSA Public Observatory and Satellite Research Center - Aurelio, Josev Michael S.; Ong, Simoun T. (Quezon City College of Architecture, University of the Philippines Diliman, 2024)
This cosmic-generative architectural study addresses pressing issues in the Philippine
space program, where space science and technology face stigmatization,
undervaluation, and reliance on non-localized and inaccessible data. Against this
backdrop, this study aims to design a public astronomical observatory and satellite
research center (SRC) to contribute to the overarching goals of the Philippine Space
Agency (PhilSA). Opportunities arise from the recent establishment of PhilSA in 2019,
and the continued support from local government and private firms, but this
unstigmatized thought has yet to reach out to the common Filipino. A public
observatory then serves as a gateway for Filipinos to the cosmos, as science tourism
and S&T advancement are inspired by user and equipment considerations for
astronomy. As such, a 3.8-hectare Greyfield site in Ilanin Forest, Subic Bay Freeport
Zone, selected for its low light pollution, seclusion, and accessibility, serves as the
canvas for this architectural initiative. This study not only endeavors to bridge
existing gaps in space R&D infrastructure but also aims to reshape perceptions,
fostering public engagement and contributing to the broader goals of sustainable
space development in the Philippines.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Observatories -- Philippines; Research facilities -- Philippines; Philippine Space Agency (PhilSA); Satellites